Report of the Subgroup on Minorities for the IX Plan Constituted by Planning Commission - Planning Commission (Planning Commission, 1996)
Area Intensive Programme: The Group Wish To Recommend The Continuation Of The Area Intensive Programme Of The Department Of Education Which, At The Moment, Covers 88 Districts (326 Blocks) Along With 5 Districts Of Assam And Pondicherry. In The Ix Plan, The Programme Should Cover All The 142 (Currently Identified) Minority Concentration Districts Of The Country. Secondly, The Group Took Note Of The Fact That The Programme As Currently Being Implemented Covers Only Educationally Backward Blocks Identified On The Yardstick Of A Minimum Of 20% Muslim Population.
Planning Commission Government of India
Planning Commission Government of India